Droplet formation at the W-macrobrush targets under transient events in ITER - Bazylev, B.N.; Landman, I.S. (Вопросы атомной науки и техники, 2007)
Most important mechanisms of melt splashing and melt bridge formation under ITER transient heat loads are analyzed. Approximate criteria for droplet ejection are used to find the range of transient events where the droplet injection is absent. The critical radius of brush edges rounding which prevents the bridge formation at the macrobrush edges is determined. Проаналізовано розвиток нестійкостей Релея-Тейлора і Кельвіна-Гельмгольца, як механізмів розбризкування розплаву при впливі перехідних теплових навантажень на диверторні пластини в ІТЕРі. Наближені критерії для ежекції крапель були використані для знаходження діапазону перехідних режимів, що не супроводжуються краплинною ерозією, і визначення критичного радіуса заокруглення границь елементів диверторних пластин типу «macrobrush». Проанализировано развитие неустойчивостей Рэлея-Тейлора и Кельвина-Гельмгольца, как механизмов разбрызгивания расплава при воздействии переходных тепловых нагрузок на диверторные пластины в ИТЭРе. Приближенные критерии для эжекции капель были использованы для нахождения диапазона переходных режимов, не сопровождающихся капельной эрозией, и определения критического радиуса закругления границ элементов диверторных пластин типа «macrobrush».